2010
DOI: 10.1007/s00436-010-2120-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Acanthamoeba spp. and other free-living amoebae in household water, Ohio, USA—1990–1992

Abstract: Knowledge of the prevalence of free-living amoebae (FLA) in US household water can provide a focus for prevention of amoeba-associated illnesses. Household water samples from two Ohio counties, collected and examined for amoebae during 1990-1992, were used to describe the prevalence of Acanthamoeba and other FLA in a household setting. Amoebae were isolated and identified by morphologic features. A total of 2,454 samples from 467 households were examined. Amoebae were found in water samples of 371 (79%) househ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 36 publications
5
58
0
1
Order By: Relevance
“…In this study, STs of isolates from hot springs, which had higher genetic diversity, were significantly different from those from cooling towers and potable water systems. These results might be due to host amoebae, which adapt to and inhabit different environments (24,25). It has been reported that the growth of L. pneumophila in host amoebae depends on the bacterial genetic background (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, STs of isolates from hot springs, which had higher genetic diversity, were significantly different from those from cooling towers and potable water systems. These results might be due to host amoebae, which adapt to and inhabit different environments (24,25). It has been reported that the growth of L. pneumophila in host amoebae depends on the bacterial genetic background (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…In our results, STs and MAb types of isolates from bathwater both differed from and were more varied than those of cooling tower water. These features might be related to the kind of host amoebae, which adapt to and inhabit various environments (20,23). It has been shown that the growth of L. pneumophila in some species of host amoebae depends on bacterial genetic background (4,8).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, similar result (88.9%) was obtained in Qalyubia governorate [23] . In other countries, a low detection rate (9.3%) was recoded in USA [25] , whereas variable rates were reported in several studies all over the world; 46.9% in Korea [26] , 23% in Nicaragua [27] , 22.79% in Brazil [28] , 29.4% and 22% in Turkey [29,30] . However, similar results were obtained on examination of household tap water samples in UK (89%) [31] and in Ohio, USA (79%) [25] .…”
Section: Discussionmentioning
confidence: 99%